DESIGN AS STRATEGY CASE STUDIES - Part 2 - Katoppo, Martin Luqman (School of Design Universitas Pelita Harapan, 2024)
JSDIS Vol. 6 Edition 1 continues the discussion of Design as Strategy case studies that began in JSDIS Vol. 5 Editions 1 and 2. JSDIS Vol. 6 Editions 1 and 2 are also special editions that are related to the National Seminar on Social Design (https://snds.uph.edu/ , https://ojs.uph.edu/index.php/SNDS/index), and the International Conference on Social Design (ICSD) (https://ojs.uph.edu/index.php/ICSD/index) which was just completed by the Faculty of Design, Pelita Harapan University on 4th-5th September, 2024. The themes raised by SNDS and ICSD 2024 are in accordance with the discussion themes of JSDIS Vol. 5, namely: Design as Strategy, with 3 sub-themes for discussion: Body of Knowledge, Innovation and Contribution to Social Change.